Nutrition intervention to prevent stunting in children aged 6-59 months - Mutiara Wahyuni Manoppo; Titih Huriah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Stunting prevention in the early years of life has become a worldwide concern in recent times. One of the prevention is to provide optimal interventions such as nutrition interventions. This study is aimed to discuss the nutritional intervention that can be given to prevent stunting. This review is according to PRISMA guidelines. This study design was a literature review conducted by searching databases PubMed, Proquest, EBSCO and Scopus from 2016-2021. The library search was developed using the PICO Logic Grid approach and the subject heading search using MeSH. The exclusion criteria in this review were studied protocol or articles review. Eight articles were included in this review. The results show nutritional interventions that can be used for stunting prevention are complementary food in the form of supplements or foods containing micronutrients and macronutrients about  4 articles and the other 4 articles that discuss the provision of supplementary feeding assistance programs and nutrition education. the nutritional interventions for stunting prevention such as providing optimal complementary food, that contain micronutrients or macronutrients or both of them and providing nutrition program such as nutrition education or assistance in planting food. Abstrak: Pencegahan stunting pada awal tahun kehidupan telah menjadi perhatian dunia belakangan ini. Salah satu cara pencegahannya adalah dengan memberikan intervensi yang optimal seperti intevensi gizi. Tujuan penelitian ini untuk membahas intervensi gizi yang dapat diberikan sebagai pencegahan stunting. Review ini sesuai dengan pedoman PRISMA. Desain penelitian ini adalah literature review yang dilakukan dengan mencari database PubMed, Proquest, EBSCO dan scopus dari tahun 2016-2021. Pencarian perpustakaan dikembangkan menggunakan pendekatan PICO Logic Grid dan pencarian judul subjek menggunakan MeSH. Kriteria eksklusi dalam review ini adalah artikel untuk studi protokol dan artikel review. Artikel yang direview berjumlah 8 artikel. Hasil menunjukkan intervensi gizi yang dapat digunakan untuk pencegahan stunting adalah makanan tambahan dalam bentuk supplement maupun makanan yang berisi micronutrient dan macronutrient sebanyak 4 artikel dan 4 artikel lainnya yang membahas tentang pemberian program pendampingan pemberian makanan tambahan dan edukasi gizi. Pemberian intervensi gizi untuk pencegahan stunting bisa berupa pemberian makanan tambahan maupun penggabungan antara program pendampingan pemberian makanan dan edukasi gizi.